2022
DOI: 10.7324/jabb.2022.100218
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extraction methods and temperature preservation on total anthocyanins compounds of Peristrophe bivalvis L. Merr leaf

Abstract: This paper proposes anthocyanins extraction from Peristrophe bivalvis L. Merr. ("lá cẩm") and preservation. Experiments were performed in water as a solvent using two different extraction methods [conventional extraction (CE) and microwave-assisted extraction (MAE)], including different solvent-to-raw material ratios, temperatures/microwave power, and times of extraction. The total anthocyanin in the extract was analyzed by UV-Vis. Multiple regression analysis was applied to analyze the influence of factors an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…A prolonged heating process may result in the degradation of thermolabile compounds [ 41 ]. Extracted anthocyanins are also easily oxidized by the environment if the extraction time is too long at high temperatures [ 42 ]. Thus, the extraction time of 10 min was chosen as the optimal extraction time for anthocyanins in pigmented corn.…”
Section: Resultsmentioning
confidence: 99%
“…A prolonged heating process may result in the degradation of thermolabile compounds [ 41 ]. Extracted anthocyanins are also easily oxidized by the environment if the extraction time is too long at high temperatures [ 42 ]. Thus, the extraction time of 10 min was chosen as the optimal extraction time for anthocyanins in pigmented corn.…”
Section: Resultsmentioning
confidence: 99%
“…The higher the ratio, the higher the total amount of solids obtained, despite the solvent used, according to mass transfer principles [45]. Since the constituents can dissolve more efficiently when there is a concentration difference between the external solvent and the inner plant cell because of the high solvent/ material ratio, the mass transfer rate and extraction yield are accelerated [25,44,46,47]. The effectiveness of ultrasonication may be related to the fact that it promotes solute 6…”
Section: Resultsmentioning
confidence: 99%
“…Phenolic compounds and antioxidation are significantly positively correlated [23,30,34]. Analytical techniques such the reducing power assay (FRAP -ferric reducing antioxidant power), nitric oxide, hydroxyl radical, hydrogen peroxide radical, and 2,2-diphenyl-1-picrylhydrazyl (DPPH) have been used to establish the substance's antioxidant ability [35,36]. Recently, comparative study of Colombo et al [2] on Italian colored rice varieties shown that the black rice cultivar has the higher antioxidant activity (DPPH assay) than the orange and non-pigmented rice varieties.…”
Section: Antioxidant Properties Of Colored Ricementioning
confidence: 99%